“Fail Fast”: The Discourse of Quality Research Perpetuated by Leadership at The Institute of Education Sciences - Bennett, Jacob; Hemmler, Vonna (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2025)
Epistemologies are understood as ways of knowing that stem from an individual’s ontological orientation. Such orientations are intimately tied to personal experiences that educational scholar Gloria Ladson-Billings (2001) argued create “systems of knowing” based on majority-normative epistemological stances. In this manuscript, we were interested in analyzing how institutional knowledge is transformed into a system of knowing based on a norming of beliefs through educational research funding. Specifically, we analyse the ways leadership within the Institute of Education Sciences (IES) conceptualizes ideas of "quality" research based on public blog posts by the institute's former director. Our results show a tilted appreciation for replicable studies based on an epistemology that understands educational research to be similar to scientific research in all fields – one centered on “rigorous reasoning” aimed at generating testable theories to expand outcomes at scale. As such, we argue such a discourse of quality research is contributing to the perpetuation, rather than amelioration, of inequities within educational settings. To end, we provide possible new directions for centering context-based epistemological understandings of quality within educational research. Such epistemologies are better suited to inform researchers who seek to close opportunity gaps in educational settings as well as increase the impact of educational research across multiple contexts.